Placenta praevia: incidence, risk factors and outcome. (2nd May 2016) - Kollmann, Martina; Gaulhofer, Jakob; Lang, Uwe; Klaritsch, Philipp
Abstract: Objective : Aim of this study was to evaluate the incidence, potential risk factors and the respective outcomes of pregnancies with placenta praevia. Methods : Data were prospectively collected from women diagnosed with placenta praevia in 10 Austrian hospitals in in the province of Styria between 1993 and 2012. We analyzed the incidence, potential risk factors and the respective outcomes of pregnancies with placenta praevia. Differences between women with major placenta praevia (complete or partial placenta praevia) and minor placenta praevia (marginal placenta praevia or low-lying placenta) were evaluated. Results : 328 patients with placenta praevia were identified. The province wide incidence of placenta praevia was 0.15%. Maternal morbidity was high (ante-partum bleeding [42.3%], post-partum hemorrhage [7.1%], maternal anemia [30%], comorbid adherent placentation [4%], and hysterectomy [5.2%]) and neonatal complications were frequent (preterm birth [54.9%], low birth weight <2500 g [35.6%], Apgar-score after five minutes <7 [5.8%], and fetal mortality [1.5%]. Women with major placenta praevia had a significant higher incidence of preterm delivery, birthweight <2500 g and Apgar-score after five minutes <7. Conclusions : Placenta praevia was associated with adverse maternal (34.15%) and neonatal (60.06%) outcome. The extent of placenta praevia was not related with differences regarding risk factors and maternal outcome.